Pendampingan Peningkatan Kapasitas Bisnis Bank Sampah Berbasis Partisipasi Masyarakat pada Kewirausahaan Kota Blitar - Puspitorini, Palupi; Serdani, Army Dita; Endrawati, Tri; Winurdana, Alfan Setya; Azzahra, Ngiza Kholiqul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Tunas Sejahtera and Sinar Berlian Waste Banks in Gedog Village, Blitar City, face the challenge of low community participation in depositing plastic waste, especially used plastic bottles. Local communities tend to manage waste independently in environmentally unfriendly ways, such as throwing it carelessly or burning it, which causes air pollution and environmental damage. Therefore, a systematic solution is needed to increase public awareness of the importance of responsible waste management. The main objective of this program is to increase community participation in depositing plastic waste to waste banks. Thus, waste can be processed into products with economic value while reducing negative impacts on the environment. To achieve this goal, several methods are used, such as counseling on waste bank management, routine plastic waste collection, and actively involving residents in the recycling process. This participatory approach is designed to make the community feel that they have a shared responsibility in maintaining a clean environment. The results of this program were that both waste banks succeeded in increasing community participation in waste bank management and significantly increasing waste management capacity.. The volume of managed waste increased from 500 kg to 1,000 kg per month, indicating that the participatory approach and logistical support are effective in improving the performance of waste banks. In addition, residents are beginning to realize the economic benefits of depositing waste, such as additional income from selling recycled materials.